Differences in Characteristics of Peripartum Patients Who Did and Did Not Require an Upgrade to the Intensive Care Unit: A Propensity Score Matching Study - Jennifer A. Walker; Jerry M. Yang; Saad Pirzada; Manahel Zahid; Samantha Asuncion; Amanda Tuchler; Gillian Cooper; Allison Lankford; Emad Elsamadicy; Quincy K. Tran (Medicina)
Background and Objectives: This study sought to identify predictors for peripartum patients admitted to non-intensive care wards who later upgraded to the Intensive Care Unit (ICU). Materials and Methods: This was a retrospective observational study of patients admitted to the Maternal Fetal Ward between 01/2017 and 12/2022, who later upgraded to the ICU. Upgraded patients were 1:1 propensity score matched with those who remained on the Maternal Fetal Ward (control). The Classification And Regression Tree, a machine learning algorithm, was used to identify significant predictors of ICU upgrade. Multivariable ordinal regression analysis was used to assess the time interval to upgrade. Results: From 1855 peripartum patients, we analyzed 37 control and 34 upgrade patients. Mean maternal age (±Standard Deviation) and gestational age for the group was 29.5 (±5.8) years and 31.5 (±7.5) weeks, respectively. The Median Sequential Organ Failure Assessment Score [Interquartile] at ward admission for the controls was 0 [0–1] versus 2 [0–3.3, p = 0.001] for upgrade patients. The Sequential Organ Failure Assessment score at Maternal Fetal Ward admission was most predictive, followed by the Acute Physiology and Chronic Health Evaluation II (APACHE II) score, and lactate dehydrogenase levels. The APACHE II score was also associated with ICU upgrade within 12 h of hospital admission (OR 1.4, 95% CI 1.08–1.91, p = 0.01). Conclusions: Compared to control patients, peripartum patients upgraded to the ICU are associated with higher physiologic scores at Maternal Fetal Ward admission. Until further studies are performed to confirm our observation, clinicians should pay attention to these physiologic scores, since they may be associated with higher-risk patients.